Respuesta :

The expansion of the given expressions are; 4x² - 5x - 5;  2x² - 13x + 15; -2x² - 5x + 3; 3x² + 6x - 1

How to simplify Quadratic equations?

A) x(x - 5) + 3x² - 5

Expanding this gives us;

x² - 5x + 3x² - 5

⇒ 4x² - 5x - 5

B) (2x - 3)(x - 5)

Expanding the function gives;

⇒ (2x² - 3x - 10x + 15)

⇒ 2x² - 13x + 15

C) -2x(x + 3) + x + 3

⇒ -2x² - 6x + x + 3

⇒ -2x² - 5x + 3

D) 3(x + 1)² - 4

⇒ 3(x² + 2x + 1) - 4

⇒ 3x² + 6x + 3 - 4

⇒ 3x² + 6x - 1

Read more about Quadratic Equations at; https://brainly.com/question/1214333

#SPJ1